Etiology of liver cirrhosis in Brazil: chronic alcoholism and hepatitis viruses in liver cirrhosis diagnosed in the state of Espfrito Santo - Goncalves, Patricia Lofego (2013)
OBJECTIVES: To report the etiology of liver cirrhosis cases diagnosed at the University Hospital in Vitoria, Espirito Santo, Brazil. METHODS: The medical charts of patients with liver cirrhosis who presented to the University Hospital in Vitoria were reviewed. Chronic alcoholism and the presence of hepatitis B or C infections (HBV and HCV, respectively) were pursued in all cases. RESULTS: The sample consisted of 1,516 cases (male:female ratio 3.5:1, aged 53.2±12.6 years). The following main etiological factors were observed: chronic alcoholism alone (39.7%), chronic alcoholism in association with HBV or HCV (16.1 %), HCV alone (14.5%) and in association with alcoholism (8.6%) (total, 23.1 %), and HBV alone (13.1%) and in association with alcoholism (7.5%, total 20.6%). The remaining etiologies included cryptogenic cases (9.8%) and other causes (6.0%). The mean patient age was lower and the male-to-female ratio was higher in the cirrhosis cases that were associated with alcoholism or HBV compared with other causes. Intravenous drug abuse and a history of surgery or blood transfusion were significantly associated with HCV infection. Hepatocellular carcinoma was present at the time of diagnosis in 15.4% of cases. Chronic alcoholism associated with HCV infection was significantly associated (p